Potential of Date Palm Fruit (Phoenix Dactylifera) for Improving Haemoglobin and Ferritin Level in Anemic Female Adolescent - Dewi Triloka Wulandari (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Anemia is one of the health problems throughout the world, especially in developing countries, which is estimated to be 30% of the world's population suffering anemia. Management of anemia is by consuming Fe tablets, but Fe tablets have side effects, namely defecation and nausea. One alternative to prevent anemia is using dates palm fruit that are rich in iron and also contain protein, fiber, glucose, vitamins, biotin, niacin, and folic acid. Date palm fruit contains complete nutrients with no side effects when given in patients with anemia. Objective To prove the program of improving hemoglobin and Ferritin levels by using Dates Palm fruit (Phoenix Dactylifera) in 14 days of female adolescent conducted in the intervention group and the control group. Method True experiment: with pretestposttest control group design. The dependent variable is the hemoglobin and ferritin level, the independent variable is dates palm fruit. The female adolescent research subjects as many as 30 respondents were divided into 15 intervention groups given Fe and Dates palm fruit and 15 control groups were only given Fe tablets. Treatment was done for 14 days. Blood measurement uses laboratory analysis. Results Dates palm fruit can increase hemoglobin levels significantly (Mean ± SD 11.76 ± 0.69 p value 0.041), while Ferritin levels did not change significantly (Mean ± SD 38.61 ± with a p value of 0.057). Conclusions and Suggestions Date Palm fruit has a lot of nutritional content used to increase hemoglobin and ferritin levels. Date palm fruit has the potential as an alternative treatment for anemia.